2010
DOI: 10.1083/jcb.201006102
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal mechanics of proplatelet maturation and platelet release

Abstract: New steps in the process of conversion of proplatelet extensions from megakaryocytes into mature platelets are defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
298
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 251 publications
(310 citation statements)
references
References 38 publications
7
298
2
3
Order By: Relevance
“…S2A), and 40% of treated cells also rapidly fragment to average sizes similar to those of large human platelets (3 to ∼4 μm). Platelets are now known to be generated by shearing of proplatelets (16), and no fragmentation was observed in untreated cells. Projection lengths up to the point of divergent fragmentation vary from 10 to ∼20 μm, which is similar to in vivo fragmented proplatelet lengths of ∼14 μm (8).…”
Section: Results and Analysismentioning
confidence: 99%
“…S2A), and 40% of treated cells also rapidly fragment to average sizes similar to those of large human platelets (3 to ∼4 μm). Platelets are now known to be generated by shearing of proplatelets (16), and no fragmentation was observed in untreated cells. Projection lengths up to the point of divergent fragmentation vary from 10 to ∼20 μm, which is similar to in vivo fragmented proplatelet lengths of ∼14 μm (8).…”
Section: Results and Analysismentioning
confidence: 99%
“…Mounting evidence that cell-cell contacts, 22,23 ECM composition 19,20 and stiffness, 21 vascular shear stress, 24,25 pO2/pH, 51,52 soluble factor interactions, 22,53 and temperature 54 contribute to proPLT formation and PLT release have suggested that recapitulating key components of BM and blood vessel microenvironments within a three-dimensional microfluidic culture system is necessary to achieve clinically significant numbers of functional human PLTs. Our microfluidic bioreactor design expands control and resolution of the microenvironment, and has allowed us to drastically improve the time to PLT release (from 18 hours down to 2 hours) and more For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…A major limitation of twodimensional liquid cultures has been their inability to account for three-dimensional BM composition and stiffness, directionality of proPLT extension, and proximity to venous endothelium. 15,24,25 Alternatively, intravital microscopy studies have provided physiologically accurate examples of proPLT production, however, poor resolution and limited control of the microenvironment has prohibited detailed study of how the BM microenvironment contributes to PLT release. 11,15 Nakagawa et al 50 recently published 3 bioreactor designs to produce human PLTs at scale from hiPSC-and ESC-derived MKs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations